CAR-T Cell Therapy: Revolutionizing Cancer Treatment - Eskandar, Kirolos; Sayh, Melad (Indonesian Society for Cancer Chemoprevention, 2024)
CAR-T cell therapy has emerged as a groundbreaking approach in cancer treatment, offering new hope for patients with refractory and relapsed malignancies. This literature review provides a comprehensive overview of the development, applications, and future directions of CAR-T cell therapy. We explore the principles behind CAR-T cell engineering, highlight the clinical successes and challenges in treating hematologic malignancies, and discuss the potential and hurdles in targeting solid tumors. The review also examines the safety profiles, including adverse effects management, and delves into the mechanisms of resistance and relapse. Furthermore, we address regulatory and ethical considerations, patient perspectives, and the innovative advancements shaping the future of CAR-T cell therapy. By synthesizing current research and clinical data, this review underscores the transformative impact of CAR-T cell therapy in oncology and its promising trajectory in the fight against cancer.Keywords: CAR-T cell therapy, cancer treatment, hematologic malignancies, solid tumors, next-generation CAR-T.